Characterization and screening of IgG binding to the neonatal Fc receptor - Neuber, Tobias (Landes Bioscience, 2014)
The neonatal Fc receptor (FcRn) protects immunoglobulin G (IgG) from degradation and increases the serum half-life of IgG, thereby contributing to a higher concentration of IgG in the serum. Because altered FcRn binding may result in a reduced or prolonged half-life of IgG molecules, it is advisable to characterize Fc receptor binding of therapeutic antibody lead candidates prior to the start of pre-clinical and clinical studies. In this study, we characterized the interactions between FcRn of different species (human, cynomolgus monkey, mouse and rat) and nine IgG molecules from different species and isotypes with common variable heavy (VH) and variable light chain (VL) domains. Binding was analyzed at acidic and neutral pH using surface plasmon resonance (SPR) and biolayer interferometry (BLI). Furthermore, we transferred the well-accepted, but low throughput SPR-based method for FcRn binding characterization to the BLI-based Octet platform to enable a higher sample throughput allowing the characterization of FcRn binding already during early drug discovery phase. We showed that the BLI-based approach is fit-for-purpose and capable of discriminating between IgG molecules with significant differences in FcRn binding affinities. Using this high-throughput approach we investigated FcRn binding of 36 IgG molecules that represented all VH/VL region combinations available in the fully human, recombinant antibody library Ylanthia®. Our results clearly showed normal FcRn binding profiles for all samples. Hence, the variations among the framework parts, complementarity-determining region (CDR) 1 and CDR2 of the fragment antigen binding (Fab) domain did not significantly change FcRn binding.